Análise da implantação e desenvolvimento do governo eletrônico brasileiro: o caso das pequenas prefeituras do Curimataú paraibano - Célio, Emiliano Rostand de Morais (2013)
The processes in the creation of a technological infrastructure that benefits the migration of public services of small prefectures, provided in person to the citizen, to the electronic medium, as well as, actions in the capacitation of the public servants and the resident population may demonstrate the level of tecnological maturity in wich they are inserted. Even so, most initiatives in online public services show lack of methodologies for assessement and measurement of performance. In reality, this void creates difficulties in the directioning of structuring and resource distribuitive actions for small prefectures, and equally prevents information registration that might subsidize comparative analysis and that may qualify the evolution and improvement of this services in a structured manner. In this dissertation is proposed the estabilishment of a general index that could enable describing the technological maturity level, representing the development of electronic government of small prefectures in the Curimataú paraibano, inserted in the Programa Nacional de Banda Larga and in the Projeto Cidades Digitais. The research was structured from a theoretical discussion about the main concepts over the Electronical Government theme, specially of its adoption by the municipal governamental sphere, equally, its mechanisms of performance evaluation, followed by the methodological procedures chosen, the results and, finally, by the final comments. As instrument, a questionnaire was used to collect eighty-one characteristics corresponding to the twenty-six variables that are part of the eight indicators of our model: infrastructure, communicability, avaliability, ease of use, accessibility, padronization, reliability and transparency. The questionnaire was applied to agents responsible for the structuring actions of these programs in the prefectures. The collecting of data resulted in twenty-three answers from these managers. The Crombach alpha (α) was used for the instrumental analysis, which demonstrated consistency in the used scales. The KMO, MSA and Barlett s sphericity tests authenticated the application of the Main Component Analysis, used in the creation of the general index. The research results indicated that the prefectures still are in the initial stages of maturity, also ponting the best and worse performances between their indicators and enabling an analytical comparison between prefectures in the same maturity levels.